Methodological Aspects of Depreciation as an Economic Category - Sigidov, Yuriy I.; Rybyantseva, Maria S.; Adamenko, Alexandr A.; Yarushkina, Elena A. (International Journal of Economics and Financial Issues, 2016)
Depreciation is a complex economic category, the essence of which is manifested in the duality: this cost element, and its own source of reproduction of fixed assets and intangible assets. The depreciation laid relationship with asset and liability balance sheet; it touches on aspects such as formation costs, taxation issues, and reproductive process. That is why a methodological study of the depreciation essence, the allocation of the classification of bases, principles and functions seems urgent. In a study of a structured approach to the treatment of depreciation, developed fourteen grounds of classification, allowing to consider a category from different perspectives. Particular attention is paid to communication of depreciation or amortization, depreciation allocated classification. Principles of depreciation and highlighted the functions performed are designed to create a more complete picture of the depreciation. Thus, the methodological aspects of the depreciation that promote, further, formation of a technique of creation and use of a sinking fund. Keywords: Amortization, depreciation, wear, reproduction process, classification, principles, functions JEL Classification: M41